2019
DOI: 10.1063/1.5129226
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction and Raman characterization of β-Ga2O3 single crystal grown by edge-defined film-fed growth method

Abstract: The crystallinity and wafer uniformity of (2¯01) and (010) oriented β-Ga2O3 substrates grown by edge-defined film-fed growth (EFG) were investigated by laboratory X-ray diffraction (XRD), synchrotron XRD, polarized Raman spectroscopy, and Raman mapping. XRD results indicated that the EFG substrates had superior crystallinity and high uniformity. Position-dependent XRD ω-rocking curves recorded across a 50.8-mm-diameter substrate had small standard deviations of δF = 1.6% for the full width at half maximum and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…But, there is a nominal peak shift observed in such Raman active vibration modes. Yao et al have reported similar findings, which is due to the localized deformation at octahedral Ga II 3+ sites than long-range bond stretching. On the contrary, asymmetric tailoring of the Raman active vibrational peaks at a higher frequency range starts appearing from x ≥ 0.2, where the interstitial accumulation of the SnO 2 phase begins overtaking the Sn incorporation process.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…But, there is a nominal peak shift observed in such Raman active vibration modes. Yao et al have reported similar findings, which is due to the localized deformation at octahedral Ga II 3+ sites than long-range bond stretching. On the contrary, asymmetric tailoring of the Raman active vibrational peaks at a higher frequency range starts appearing from x ≥ 0.2, where the interstitial accumulation of the SnO 2 phase begins overtaking the Sn incorporation process.…”
Section: Resultsmentioning
confidence: 62%
“…Additionally, there are several reports in the recent literature suggesting the same theoretical prediction. 52 , 53 Moreover, decreasing peak intensity, related to the mid-frequency range (320, 346, and 415 cm –1 ), with increasing Sn concentration confirms selective Sn incorporation at Ga II 3+ sites. But, there is a nominal peak shift observed in such Raman active vibration modes.…”
Section: Resultsmentioning
confidence: 77%
“…[31][32][33][34][35] Likewise, pure vdW junction between metallic TMDs and β-Ga 2 O 3 seems unlikely in the present study. Figure 1b [36][37][38] Atomic force microscopy (AFM) to measure thickness of Nb(Ta)S 2 and β-Ga 2 O 3 has been conducted with MESFET structure, and exemplary 3D thickness profiles are thus shown in Figure 1c,d in literature (qΦ W of NbS 2 , [39,40] TaS 2 , [39,41] and β-Ga 2 O 3 [2,3] ≈6.0, ≈5.6, and ≈4.1 eV, respectively). Such difference is attributed to possible existence of ultrathin oxide (NbO x or TaO x ) on TaS 2 or NbS 2 , since those TMDs are so weak to oxidation in air ambient.…”
Section: Introductionmentioning
confidence: 99%
“…While the Au and Bu modes are infrared active, 30 A g and B g are Raman active. Different factors lead to various Raman peaks.…”
Section: Resultsmentioning
confidence: 99%